Comparison of the Efficacy of Piperacillin/Tazobactam and Meropenem, with or without Intravenous Immunoglobulin, as Second-Line Therapy for Febrile Neutropenia: A Prospective, Randomized Study - Hirozumi Sano; Ryoji Kobayashi; Satoru Matsushima; Daiki Hori; Masato Yanagi; Koya Kodama; Daisuke Suzuki; Kunihiko Kobayashi (The Korean Society of Pediatric Hematology-Oncology, 2021)
Background : : Febrile neutropenia (FN) remains an important complication in pediatric cancer patients. The present study compared the efficacy of meropenem (MEPM) and piperacillin/tazobactam (PIPC/TAZ) with or without intravenous immunoglobulin (IVIG) as second-line therapy for FN in pediatric patients. Methods : : As first-line treatment for FN, 394 episodes in 99 patients were randomly assigned to receive PIPC/TAZ (360 mg/kg/day, maximum 18 g/day) or MEPM (120 mg/kg/day, maximum 3 g/day). Eighty-four episodes in 42 patients were judged as failures, and, thus, were enrolled for second-line treatment. In second-line treatment, antibiotics were switched to MEPM or PIPC/TAZ, and episodes were further randomized for treatment with or without concomitant IVIG at 100 mg/kg/day (maximum 5 g/day) for 3 consecutive days. Results : : The total success rate of second-line treatment was 50.0% (52.0% in PIPC/TAZ and 47.2% in MEPM with or without IVIG, P=0.826). The success rates of patients treated with (IVIG+ group) and without IVIG (IVIG− group) were 53.8 and 46.7%, respectively (P=0.662). In the IVIG+ group, the success rate of patients younger than 8 years old was 78.6%, which was significantly higher than that of those aged 8 years and older (40.0%, P=0.043). Conclusion : : PIPC/TAZ and MEPM were equally effective as second-line treatment. Concomitant IVIG was also effective, particularly in patients younger than 8 years.